Assessing Renewable Energy Project Efficiency through Green Sukuk: Evidence from Indonesia and Malaysia - Sri Ulfa; Tri Wahyuningsih; Rani Surya Resiana (Universitas Islam Internasional Indonesia, 2026)
Amidst global climate challenges, green sukuk has emerged as a shariah-compliant instrument to finance renewable energy projects, supporting the Sustainable Development Goals (SDGs) in Organisation of Islamic Cooperation (OIC) countries such as Indonesia and Malaysia. This study examines the impact of green sukuk structures on the efficiency of renewable energy projects. While existing literature has broadly discussed the effects of green sukuk, a significant gap remains in their quantitative assessment of efficiency, particularly in an approach that integrates both financial cost-effectiveness and operational performance. This study explicitly addresses this gap by developing a novel framework that integrates cost-effectiveness analysis (CEA) and data envelopment analysis (DEA) to evaluate four prominent green sukuk: Indonesia’s Green Sovereign Sukuk 2018 and 2019, and Malaysia’s Tadau Energy Sukuk 2017 and Quantum Solar Park Sukuk 2018, using data from official reports and prospectuses. Results show the Green Sovereign Sukuk 2018 as the most efficient (2.90 MW/USD million, 1,600-ton CO₂/USD million, DEA score 1.0000), driven by large-scale implementation and centralized governance, whereas Quantum Solar 2018 scored lowest (0.61 MW/USD million, 808.08-ton CO₂/USD million, DEA score 0.5051) due to project fragmentation. Ijarah contracts enhance governance, whereas mudharabah fosters adaptability but increases risk. The study concludes that hybrid contracts (e.g., musharakah-murabahah) and balanced regulations can optimize the efficiency of green sukuk, offering a scalable model for OIC countries to advance sustainable financing aligned with ESG and SDG objectives.